Non-traditional risk factors of progression of chronic kidney disease in adult population: a scoping review - Diana Lorena Cisneros-García; Elena Sandoval-Pinto; Rosa Cremades; Adrián Ramírez-de-Arellano; Mariana García-Gutiérrez; Roberto Martínez-de-Pinillos-Valverde; Erick Sierra-Díaz; Erick Sierra-Díaz (Frontiers in Medicine, 2023)
Chronic kidney disease (CKD) has become a public health concern over the last several years. Nowadays developed countries spend around 3% of their annual health-care budget on patients with CKD. According to the scientific community the most remarkable risk factors for CKD are diabetes and hypertension. Unknown CKD etiology has been reported as a global phenomenon including uncommon risk factors such as: dehydration, leptospirosis, heat stress, water quality, and others. This study aims to report non-traditional risk factors for ESRD based on a scoping review methodology. The scoping review methodology described by Arksey and O’Malley was used by performing an extensive review of the information. A total of 46 manuscripts were reviewed. The non-traditional ESRD risk factors are depicted based on six categories. Gender and ethnicity have been considered as risk factors for ESRD. Erythematous systemic lupus (ESL) is reported as an important risk factor for ESRD. Pesticide use has been an significant risk factor due to its effects on human and environmental health. Some compounds commonly used in homes against insects and plants are related to ESRD. Congenital and hereditary diseases in the urinary tract have been studied as a cause of ESRD in children and young adults. End-stage renal disease is a major concern for public health on a global level. As it can be seen, non-traditional risk factors are several and have different etiologies. It is necessary to put the issue on the table and add it to the public agenda in order to find multidisciplinary solutions.